Decisions taken by States with authoritarian governments: economic basis and perspectives on SDG 16 - Armando Alvares-Garcia Júnior (Revista Iberoamericana de Estudios de Desarrollo)
This article initially analyses the theoretical possibility that the terms «rule of law» and «human rights» in the Treaty on European Union (TEU) can be analysed from the perspective of the Economic Analysis of Law (EAL). It then focuses on the economic principles underlying decision-making to appreciate, under that perspective, the choices made by States, both at the national and international level (which could also include the commitment to the SDGs). From there, the study is oriented more towards SDG 16 proposing, summarily, to denominate with the terms «horizontal» and «vertical» two different basic perceptions on its three main areas (peace, justice, and strong institutions) and tentatively uncovering their possible impacts on the rule of law and the rights and freedoms of specific groups (e.g., LGBTQIA+ community, immigrants, refugees, etc.). It is suggested that, while the «horizontal perception» presents a socially inclusive role, the «vertical perception» tends to be more exclusionary. Seeking congruence with the above, it is also suggested that a biased perception of SDG 16 (associated with the «vertical» vision) could help authoritarian States in the exaltation of their nationalism, without forgetting that international public order, often wielded as an expression of national sovereignty, can serve as a «defensive shield» against alleged «attempts to alter» the fundamental values of the State and of the Christian roots of their societies. Simultaneously, observation of everyday political life seems to suggest that public order can be altered to the liking of populist political parties. The result seems to reveal a growing dichotomy between values (European vs. national), public orders (European, albeit incipient vs. international and domestic), and types of democracy (liberal vs. illiberal). As incidental and illustrative examples, the authoritarian drifts in Hungary and Poland are included in the study.